2014
DOI: 10.9755/ejfa.v26i4.16178
|View full text |Cite
|
Sign up to set email alerts
|

Fast protein liquid chromatography of camel ?-lactalbumin fraction with radical scavenging activity

Abstract: The aim of this study was to investigate the radical-scavenging properties towards a stable radical cation, ABTS, of Camelus dromedarius whey proteins (CWP) separated onto a cation-exchanger by fast protein liquid chromatography. The highest activities were found for CWP and fraction F1 mainly composed of α-lactalbumin. Fractions F2, F3 and F4 contained a mixture of lactoferrin, immunoglobulins G and probably camel whey basic protein (CWBP). These three fractions displayed low radical-scavenging activities. La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…At high salt concentration α‐lactalbumin might present on form native‐like molten globule, whereas other molten globules are probably present on form of structurally less defined states (Pettersson et al., 2006). Particular study revealed that enriched fraction with α‐lactalbumin of camel whey protein that was purified further by cation‐exchange chromatography exhibited efficient antioxidative property, whereas other fractions mainly composed of heavy‐chain immunoglobulins might serve significant interest for human therapy by modulating immune‐response for example (Halima et al., 2014). It was demonstrated that α‐lactalbumin of whey protein has a pronounced suppressive effect against the increased release of proinflammatory cytokines like IL‐1 and IL‐6 and ischemia/reperfusion‐induced intestinal injury in a rat model in addition to suppressive effect to tumor necrosis factor‐α from the d ‐galactosamine induced liver‐injury in a rat model (Yamaguchi & Uchida, 2007).…”
Section: Alpha‐lactalbuminmentioning
confidence: 99%
“…At high salt concentration α‐lactalbumin might present on form native‐like molten globule, whereas other molten globules are probably present on form of structurally less defined states (Pettersson et al., 2006). Particular study revealed that enriched fraction with α‐lactalbumin of camel whey protein that was purified further by cation‐exchange chromatography exhibited efficient antioxidative property, whereas other fractions mainly composed of heavy‐chain immunoglobulins might serve significant interest for human therapy by modulating immune‐response for example (Halima et al., 2014). It was demonstrated that α‐lactalbumin of whey protein has a pronounced suppressive effect against the increased release of proinflammatory cytokines like IL‐1 and IL‐6 and ischemia/reperfusion‐induced intestinal injury in a rat model in addition to suppressive effect to tumor necrosis factor‐α from the d ‐galactosamine induced liver‐injury in a rat model (Yamaguchi & Uchida, 2007).…”
Section: Alpha‐lactalbuminmentioning
confidence: 99%